Modern Drama :Defining the Field - Knowles, Ric, Ed (University of Toronto Press, 2003)
Theatre, like other subjects in the humanities, has recently undergone quintessential changes in theory, approach, and research. Modern Drama - a collection of twelve essays from leading theatre and drama scholars - investigates the contemporary meanings and the cultural and political resonances of the terms inherent in the concepts of 'modern' and 'drama,' delving into a range of theoretical questions on the history of modernism, modernity, postmodernism, and postmodernity as they have intersected with the shifting histories of drama, theatre, and performance. Using incisive analyses of both modern and postmodern plays, the contributors examine varied topics such as the analysis of periodicity; the articulation of social, political, and cultural production in theatre; the re-evaluation of texts, performances, and canons; and demonstrations of how interdisciplinarity inflects theatre and its practice.